Synthesis and Evaluation of New Thiazolyl Hydrazone Derivatives as Potential Anticancer Agents - Asım Kaplancıklı, Zafer; Sever, Belgin; Dilek Altıntop, Mehlika; Atlı, Ozlem; Baysal, Merve; Ozdemir, Ahmet (Letters in Drug Design & Discovery, 2017)
Background: In recent years, thiazole derivatives incorporated with hydrazone moiety have attracted a great deal of interest due to their pivotal role in the field of current cancer research. Methods: In the present study, new thiazolyl hydrazone derivatives were synthesized via the reaction of 1-(4-phenylcyclohexylidene)thiosemicarbazide with 2-bromoacetophenone derivatives. MTT assay was performed to assess the cytotoxic effects of the compounds on A549 human lung adenocarcinoma, HepG2 human liver hepatocellular carcinoma and C6 rat glioma cell lines. The selectivity of the compounds was investigated using NIH/3T3 mouse embryonic fibroblast cell line. Results: 4-(4-Methylsulfonylphenyl)-2-(2-(4-phenylcyclohexylidene)hydrazinyl)thiazole (7) was found to be the most promising anticancer agent against HepG2 cell line with an IC50 value of 0.316 mM when compared with cisplatin (IC50=0.091 mM). Compounds 2 and 6 also exhibited cytotoxic effects on HepG2 cell line with IC50 values of 0.81 mM and 0.79 mM, respectively. Besides, compounds 2, 6 and 7 did not show any cytotoxicity against NIH/3T3 cell line. Conclusion: In particular, compound 7 was found to be a potent anticancer agent to go further studies due to its selective antitumor activity against HepG2 cell line.
Keywords: hydrazone